ELF feito no Brasil: Expanding Theoretical Notions, Reframing Educational Policies - Duboc, Ana Paula; Siqueira, Sávio (Status Quaestionis, 2020)
ELF studies have long established itself as a solid field of inquiry much as a response to the pioneering work of scholars such as Jenkins (2000; 2007; 2009; 2015) and Seidlhofer (2001; 2005; 2011). Its ripple effect in the last decades is made present mainly among European scholars who have highly contributed to the consolidation of the area. By embracing the decolonial notion of epistemic pluralism (Sousa Santos, 2007; 2018), this paper wishes to turn knowledge production on ELF of the global South visible. In doing so, we present a brief state-of-the-art on recent ELF research in Brazil, followed by an analysis on how such theoretical framework echoes in the recently launched Brazilian National Common Core Curriculum (BNCC) (Brasil 2017). As a country deeply forged under colonialism, coloniality traces are still strongly present in Brazil. By departing from decolonial studies (Castro Gómez 2007; Quijano 2007; Mignolo 2000; 2007; 2009a; 2009b; Walsh 2018), the expression ELF feito no Brasil (Duboc 2019) attempts to stress the expanding notion of ELF by contemporary Brazilian scholars who have put greater emphasis on the critical and political nature of English. Along with the increase in ELF studies in Brazil comes the need to analyze the place of ELF within the aforementioned BNCC, in particular, the very epistemological conflict that emerges from a standardized, top-down curriculum framed by a more fluid notion of language (Duboc 2019). In line with Bakhtinian thought, which acknowledges the dialogical and heteroglot nature of language, this paper advocates in favor of such epistemological conflicts, be them within the ELF research field or in ELF-based educational policies.